2012
DOI: 10.1002/ejic.201200471
|View full text |Cite
|
Sign up to set email alerts
|

Selective Consecutive Insertion of Alkynes into the B–Se Bonds of 1,3,2‐Diselenaborolane Derivatives: Synthesis and Molecular Structures of Nine‐Membered Rings

Abstract: Various alkynes have been inserted selectively and stepwise into the B-Se bond(s) of 1,3,2-diselenaboracyclopentanes {as the 4,5-[1,2-dicarba-closo-dodecaborano(12)] derivatives}. The B-phenyl derivative was much less reactive than the Bhalogeno derivatives. The proposed structures were confirmed in solution by multinuclear NMR studies ( 1 H, 11 B, 13 C and 77 Se NMR), also supported by DFT calculations of the gas-phase molecular geometries and NMR parameters [B3LYP/6-311+G(d,p) level of theory]. Isotope-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…1,1‐Carboboration of dialkynyl‐ and tetraalkynylsilanes opens a convenient route to cyclic silanes such as siloles 60 or bisiloles 56 . The reaction with alkynyl(diorgano)tin compounds (R 1 2 Sn(C≡C‐R 2 ) 2 leads to boron‐functionalized 4‐stannabora‐cyclohexa‐2,5‐dienes although rather harsh reaction conditions (heating for a long period at 100–120 °C) are required when trialkylboranes (BR 3 ; R=Me, Et), Et‐9‐BBN, BPh 3 , and B(C 6 F 5 ) 3 are used . Organometallic‐substituted allenes obtained by 1,1‐organoboration of bis(trimethylstannyl)ethyne with trimethylsilyl‐ and dimethylsilyldialkylboryl‐substituted alkenes have been reported by Wrackmeyer .…”
Section: Preparation Of Boron‐substituted 13‐dienesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,1‐Carboboration of dialkynyl‐ and tetraalkynylsilanes opens a convenient route to cyclic silanes such as siloles 60 or bisiloles 56 . The reaction with alkynyl(diorgano)tin compounds (R 1 2 Sn(C≡C‐R 2 ) 2 leads to boron‐functionalized 4‐stannabora‐cyclohexa‐2,5‐dienes although rather harsh reaction conditions (heating for a long period at 100–120 °C) are required when trialkylboranes (BR 3 ; R=Me, Et), Et‐9‐BBN, BPh 3 , and B(C 6 F 5 ) 3 are used . Organometallic‐substituted allenes obtained by 1,1‐organoboration of bis(trimethylstannyl)ethyne with trimethylsilyl‐ and dimethylsilyldialkylboryl‐substituted alkenes have been reported by Wrackmeyer .…”
Section: Preparation Of Boron‐substituted 13‐dienesmentioning
confidence: 99%
“…The main product is the (Z)i somer. [22][23][24] The reaction is initiated by ac leavage of the polar metalÀcarbonb ond by the electron-deficient boron atom to form an alkynylboratelike zwitterionic intermediate, followedb yt he 1,2-shift of one organyl group from boron to the neighboring alkynyl carbon atom,l eadingt ot he organometallic-substituted alkene product substituted with an element from roup 14 of periodic table as wella ss ome other metals such as Ti andP t. [25][26][27][28][29] Early prog-ress was made by the conversion of BR 3 into trialkyl(alkynyl)borates [R 3 BÀCCÀCÀR 2 ] À ,f ollowed by their reactionw ith electrophilesa nd salt elimination57.T he application of alkenylmetalloidso rd ialkynylmetalloids in carboboration process is also an effective method for obtainingb oronate-substituted 1,3dienes 58 (Scheme 17).…”
Section: Organoboration (Carboboration)ofa Lkynesmentioning
confidence: 99%
“…91 The XE{1,2-Se 2 C 2 B 10 H 10 } (E = B or P, X = halide) clusters were synthesised and demonstrated to undergo alkyne insertion into the B-Se bonds of the borolane moiety. 92,93 Metallaboranes, metallaheteroboranes and exo-metallaheteroboranes A number of new transition metal centred boron molecular wheels have been observed, including [MrB 9 ] À (M = Rh or Ir, compounds VII and VIII) and [M 0 rB 10 ] À (M 0 = Nb or Ta), the first deca-coordinated 2D structures. 94 Photoelectron spectroscopy suggested that the former have stable neutral forms, MrB 9 .…”
Section: Annual Reports a Reviewmentioning
confidence: 99%
“…Starting from the parent ortho ‐carborane 3 , careful preparation of 4 and 5 enabled the synthesis of diselenasila cycles in good yield and high purity,4c as shown for 6 in Scheme . Such diselenasila cycles turned out to be useful starting materials for the synthesis of other novel heterocycles, since the Si–Se bonds are readily split in exchange reactions with various element halides 2022…”
Section: Introductionmentioning
confidence: 99%